On the relation between 'resilience' and 'smartness': A critical review. (1st June 2022) - Cañavera-Herrera, Juan Sebastián; Tang, Junqing; Nochta, Timea; Schooling, Jennifer M.
Abstract: Cities continue to face significant challenges that test their capacity for resilience. With the development of smart cities, there needs to be a better understanding of how the introduction of smart technologies will affect urban resilience. To address this issue, this article presents a critical review of the literature on smart cities and smart technologies focussing on representations of resilience. The findings reveal that discussing resilience in relation to smart city components of the data layer, digital technologies and the physical city can provide some degree of clarity despite the existence of a multiplicity of definitions and interpretations. Furthermore, the analysis indicates that the nature of relationships between 'smartness' and 'resilience' remains contested, and largely dependent on the perceived role of digital technologies in resilience-building processes. This in turn is influenced by how these technologies are used and what the intention and expectations are in relation to their use. In order to address these issues, we conclude that further interdisciplinary research, extending to the physical, social and environmental systems of cities, is needed to better understand the relations between smartness and resilience.